1993
DOI: 10.1063/1.353058
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants and thermal expansion coefficient of metastable C49 TiSi2

Abstract: The elastic constants and thermal expansion coefficient of C49 TiSi2 thin films have been investigated by in situ curvature measurement during heat treatment and ex situ x-ray diffraction measurements. The C49 TiSi2 compound was formed from Ti-Si multilayers deposited on monocrystalline silicon and sapphire substrates. The films were polycrystalline without any evident texture. Young’s modulus (142 GPa), Poisson’s ratio (0.27), and the thermal expansion coefficient (10.9×10−6 K−1) have been determined. Note th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The difference between our results and experiment [34,35,17,[36][37][38][39][40] is less than 1% for lattice constants and 10% for elastic constants.…”
Section: Details Of Calculationmentioning
confidence: 61%
“…The difference between our results and experiment [34,35,17,[36][37][38][39][40] is less than 1% for lattice constants and 10% for elastic constants.…”
Section: Details Of Calculationmentioning
confidence: 61%
“…There are some theoretical research works to predict the elastic moduli of the TiSi 2 , for example, E = 277.8 GPa for ideal polycrystalline TiSi 2 compounds [7], E = 255.6 GPa for polycrystal conglomerates [8] and bulk modulus 176.4 GPa for C54 TiSi 2 [17]. Jongste et al obtained the elastic modulus 142 GPa for C49 film by X-ray diffraction [5]. It is found that these results are quite comparable with most of our measurement results reported above.…”
Section: Young Modulus Of Tisi 2 Nanowirementioning
confidence: 99%
“…Titanium disilicide is among the most popular ones, which exhibits high melting temperature, relatively low density, the lowest resistivity (for C54 phase) [1] and good oxidation resistance at a high temperature. The film and bulk materials of titanium disilicide have been extensively studied, such as formation and phase transformation [1][2][3], electrical characterization [4], thermal expansion coefficient [5] and so on. Mechanical analysis, e.g., Young modulus and Poisson ratio of C49 polycrystalline film [5], the in situ stress of titanium silicide films during sintering [6], elastic constants of transition-metal-disilicide single crystals [7], and elastic properties, yield stress for sintered compound of TiSi 2 [8], was also more or less reported experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the magnified diffractograms shown in Fig. 1(b), two TiSi 2 phases (PDF #04-007-1144 and #04-002-1352, the latter being a metastable phase formed prior to the stable orthorhombic phase 36 ) were observed and possibly minute amounts of a high temperature Ti phase (PDF #00-044-1288). These observations are consistent with a scenario in which the TiO 2 reacts with Mg 2 Si or elemental Si present in the sample to form MgO, TiSi 2 and possibly Ti.…”
Section: Structural Characterization Of Prepared Materialsmentioning
confidence: 99%